(3LGeY GdCUhd dCMGOjK GdQShds - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s
(3ChdgG (B:s
(3MQa GdgGA , hjTJed Ydi KdGKI cJH s
(3BNQgG (B:s
(3eHJhQ , hBNQ GdehLhO efg jfJgi ai GdaUd GdQGHY ef GdaQY GdKGfi ai GdfSH Hbhdg (B: (3GdRGZhfi HGdZjf GdeYLeI hVegG hGdfhf efShH Edi GdRHjOi HVe GdRGi haJM GdHGA GdehMOg s
(3GdLRA GdSGHY ef GdfSNI GdSGHbI (B"s
(3HMhGTjgG JYdjbGJs
(3hcJHJ GdYfhGfGJ HGdMeQI hGdfSNI ebGHdI Ohf JGQjNs
(3HBNQgG bQGAI SfI (B894 (3g` s
(3GdfSNI HgG MhGT s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs